Body and Social violence - Suleiman, Myrna (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Human being is brought through a living biological membership, which is made up of various cultural and societal conditions. One of these conditions is what constitutes coercive forces that affect him and make him alienated from himself. He is physically and morally oppressed him, treated him as a commodity, and is seen as a slave, not a master of himself. When civilization works to provide comfort, it makes it ask for freedom from it and subject to its conditions at the same time. The status of women is especially seen as a body obscured as the honor of women is in her body, or as a beautiful body when it meets the requirements of fashion, while it is self-sufficiency and treated as an economic commodity subject to supply and demand and profit and loss .In all of the above, the role of the religious and political discourse and its authority on the body is manifested. Both of these speeches call for the liberation of the body and the preservation of its dignity based on criteria that are worthy of being followed from its point of view. The research concludes that the human consciousness of dignity is one consciousness in which the self is not separated from its body, and man is a sophisticated entity that interacts in its composition with the physical material on the one hand and the various societal conditions on the other hand.